A NEW CONTROL CHART FOR PROCESS MONITORING BASED ON THE UNIFIED CAPABILITY INDEX - ADEOTI, Olatunde A (MATTER: International Journal of Science and Technology, 2019)
Control charts based on capability index for monitoring process parameters have received wide attention recently. In this paper, we proposed new control charts for online monitoring of the process mean and variability using a unified capability index approach. Control chart coefficients are given for constructing the unified capability index-based mean ( ) and standard deviation (S) control charts. Real life data is given to demonstrate the advantages of the proposed control charts over the standard mean ( ) and standard deviation (S) charts for process monitoring. The results of study showed that the proposed unified capability index-based control charts outperform the standard and S control charts and it is efficient for simultaneous monitoring of process stability and measuring the capability of the process to meet specification.